Red House (Govt. Buildings), Trinidad, B.W.I. - (:unkn) unknown (James Book Store, 2010)
Exterior view of the Red House located in Port of Spain, Trinidad and built in the neoclassical architectural style, Beaux Arts.
Colour: Green, Blue, Grey, Brown and White; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Public buildings--Trinidad and Tobago; Windows--Trinidad and Tobago; Streets--Trinidad and Tobago; [1900]; Historic buildings--Trinidad and Tobago; Buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Red House, The (Trinidad and Tobago); Parliament Building (Trinidad and Tobago)